Demorest Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1883)
Summer Melodies--Out of the World--Smith College: Social Life--A Noted Picture Gallery--The Tsory of Hereward Leofricsson, Last of the English--The Water Witch--Satisfied--A Perfect Fright--Death--A Chicken Sermon--The Paupers of Pompeii--Almost a Tragedy--The Rosicrucian--The Head of Perseus--The Rose in Song and Story--The Little Bride--A Buried City--How We Live in New York--The Education of Women--Elizabeth Thompson Butler--Friends and Foes--New Occupations for Home--Holy Cross Mountain in Colorado--What Women Are Doing--The World's Progress--Kitchen--Scientific--Review of Fashions: July
Demorest's Family Magazine. July 1883. Vol. 19, No. 9. New York: W. J. Demorest, 1883. Valdosta State University Archives and Special Collections
Keywords: Summer Melodies--Out of the World--Smith College: Social Life--A Noted Picture Gallery--The Tsory of Hereward Leofricsson, Last of the English--The Water Witch--Satisfied--A Perfect Fright--Death--A Chicken Sermon--The Paupers of Pompeii--Almost a Tragedy--The Rosicrucian--The Head of Perseus--The Rose in Song and Story--The Little Bride--A Buried City--How We Live in New York--The Education of Women--Elizabeth Thompson Butler--Friends and Foes--New Occupations for Home--Holy Cross Mountain in Colorado--What Women Are Doing--The World's Progress--Kitchen--Scientific--Review of Fashions: July